Leflunomide Induced DRESS Syndrome: A Case Report - S Parajuli; D Chaudhary; S Pandey; S Baral; D B Pokhrel (Nepal Journal of Dermatology, Venereology & Leprology)
DOI: http://dx.doi.org/10.3126/njdvl.v10i1.6423